Integrating Features of Islamic Traditional Home and Smart Home - El Basyouni, Mona (Journal of Islamic Architecture, 2017)
Architecture is a mirror that reflects the various elements of its environment and surroundings, such as climate, geographical characteristics, standard architectural principles, and social, cultural and scientific developments. Muslims of different regions were able, through architecture, to portray their temperaments and environments, free of external influence and guarantee life goals for users. Every day, building owners and occupants experience the constant challenges of comfort, convenience, cost, productivity, performance and sustainability. Owners, designers, builders, and operators are continuously faced with new processes, technologies and offerings to help them achieve better building performance. Since an intelligent building is run by a â€œsystem of systemsâ€ that is integrated to deliver a higher level of operational efficiency and an improved set of user-interface tools than are usually found in traditional building automation; at the other handÂ Arab homes with Islamic Identity guarantee all life goals for use.. Hence, this research focus on the smart environmental treatments of Islamic features for traditional architecture in Arabs homes, features of smart home and life goals for resident users.Trying to achieve a methodology combining them for enriching Arab experience of traditional architecture and its architectural results, with the modern trends of smart architecture. This combination aims at creating a residential model combining the benefits and features of Arab Islamic identity and intelligent design.Â